More than Copy and Paste. The Drafting of the Judicial Order in the Decrees of the Third Mexican Council - Osvaldo Rodolfo Moutin (Rechtsgeschichte - Legal History, 2016)
This article compares the legislation promulgated by the Synod of Granada (1572) and the Third Mexican Provincial Council (1585) regarding procedural canonical law. Diego Romano, bishop of Puebla, served as a vehicle between the Spanish and Mexican Assemblies, and he was clearly inspired by the former when drafting the latter. The article pays attention to the level of appropriation and via a comparison of the texts addresses the question whether it is possible to say that Iberian procedural law was copied by the prelate.